THE IMPACT OF TEAM TEACHING ON STUDENT ACHIEVEMENT AND PERCEPTIONS IN AVIATION VOCATIONAL SCHOOLS - Rochmawati, Laila; Sylvia, Tiara; Diriyanti Novalina , Susi (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2024)
This research highlights the significance of collaborative teaching in addressing the diverse learning challenges faced by cadets, as statistical analysis indicates that team teaching strategies can significantly enhance English learning outcomes compared to traditional methods, thus supporting the educational rights of all students. The research aims to investigate the differences in academic performance between students taught using team-teaching strategies and traditional teaching methods in vocational aviation schools, employing a quantitative ex post facto comparative analysis to measure the impact of these teaching strategies on English learning outcomes, supported by statistical data from Polytechnic Penerbangan Surabaya and Polytechnic Penerbangan Medan. Our findings indicate a statistically significant difference in academic performance, with team teaching students achieving higher average scores (M = 85.4, SD = 3.2) compared to traditional teaching students (M = 78.6, SD = 4.1), p < 0.05. The collaborative nature of team teaching promotes professional development among educators, leading to improved instructional strategies and teaching quality. Educators are encouraged to adopt team teaching strategies to enhance student engagement and learning outcomes, as evidence demonstrates their effectiveness in fostering a more inclusive and supportive educational environment.